PROJECT BASED WORKSHEETS ON BIOPLASTIC MAKING - Septi Alawiyah; Cucu Zenab Subarkah; Saepudin Rahmatullah (Gunung Djati Conference Series, 2021)
Banana peels contain starch, which is a natural polymer, so it can be used as a base for bioplastics. The purpose of this study is to describe the appearance of product results that have been tested for validation, development of project-based worksheets. Project-based worksheets can be used in practicum learning activities. This research method uses DBR (Design Based Research), with four stages, namely analysis, product design development, product testing, product validation. The experimental procedure in this study was carried out in two stages, namely the stage of making starch flour, the stage of making bioplastic films. The validation test stage is carried out by validators who are experts in the field of learning media and synthetic polymer materials. The results of the validation test mean that the rcount of the worksheet displays is 0.905, the content of the worksheet material is 0.815, and the language in the worksheet is 0.866. This is a project-based worksheet every aspect of the worksheet assessment is declared valid, and this project-based worksheet is suitable for use as a learning medium.